Adipose-Derived Stem Cells for Regenerative Wound Healing Applications: Understanding the Clinical and Regulatory Environment. (13th August 2019) - Luck, Joshua; Weil, Benjamin D; Lowdell, Mark; Mosahebi, Afshin
Abstract: There is growing interest in the regenerative potential of adipose-derived stem cells (ADSCs) for wound healing applications. ADSCs have been shown to promote revascularization, activate local stem cell niches, reduce oxidative stress, and modulate immune responses. Combined with the fact that they can be harvested in large numbers with minimal donor site morbidity, ADSC products represent promising regenerative cell therapies. This article provides a detailed description of the defining characteristics and therapeutic potential of ADSCs, with a focus on understanding how ADSCs promote tissue regeneration and repair. It summarizes the current regulatory environment governing the use of ADSC products across Europe and the United States and examines how various adipose-derived products conform to the current UK legislative framework. Advice is given to clinicians and researchers on how novel ADSC therapeutics may be developed in accordance with regulatory guidelines.